Risk factors for admission and length of stay in hospital for children with and without congenital anomalies: A EUROlinkCAT study - Joanne Given; Ester Garne; Joan Morris; Maria Loane; EUROlinkCAT Working Group (International Journal of Population Data Science, 2023)
Objective To explore risk factors for hospital admission, and length of stay (LOS) in hospital, among children with congenital anomalies (CAs) and reference children without CAs in Europe.